2012
DOI: 10.1111/j.1600-0501.2012.02456.x
|View full text |Cite
|
Sign up to set email alerts
|

Healing outcomes at implants installed in sites augmented with particulate autologous bone and xenografts. An experimental study in dogs

Abstract: Particulate autologous bone as well as DBBM particles used to augment horizontally the alveolar bony process allowed for the osseointegration of implants installed after 3 months of healing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 27 publications
0
21
0
Order By: Relevance
“…; De Santis et al. ). Therefore, there is no clear rationale to support placement of the autogenous layer on the inside, in apposition with the implant.…”
Section: Discussionmentioning
confidence: 98%
“…; De Santis et al. ). Therefore, there is no clear rationale to support placement of the autogenous layer on the inside, in apposition with the implant.…”
Section: Discussionmentioning
confidence: 98%
“…De Santis et al 14) reported the results of implant placement into contemporaneous mandibular defects. The implant and autologous bone were simultaneously placed on one side, while another implant was placed on the other side following autologous bone block grafting.…”
Section: Discussionmentioning
confidence: 99%
“…In a recently published report on an experiment in dogs (De Santis et al. ), implants were installed in augmented bone, and very thin buccal bony walls were found at the time of implant installation. Despite this, a low degree of vertical buccal bone resorption was found.…”
mentioning
confidence: 99%
“…A minimum width of the buccal bony ridge, of approximately 2 mm, was suggested for implant installation to minimize resorption (Spray et al 2000). In a recently published report on an experiment in dogs (De Santis et al 2012), implants were installed in augmented bone, and very thin buccal bony walls were found at the time of implant installation. Despite this, a low degree of vertical buccal bone resorption was found.…”
mentioning
confidence: 99%